Starizem v zdravstvenih ustanovah - Lešnik, Amadeus (Obzornik zdravstvene nege, 2017)
Introduction: Ageism is discrimination and prejudice against the elderly based on stereotypes related to their chronological age. The purpose of the study was to establish whether the elderly can feel ageism in a clinical setting and how it affects them. Methods: A descriptive quantitative study was conducted in a healthcare institution on a convenience sample of 132 elderly aged 65 to 90 years. A questionnaire based on the literature review with 11 closed-type questions was used. The presence of ageism and the degree of affectedness was measured with a three-digit number scale. A descriptive univariate and bivariate (hi-square test for independent samples) analysis was used for the description of the sample and a systematic representation of the answers to the research questions. Results: In total, 319 discriminatory events were detected. From 132 respondents, at least one discriminatory event was experienced by 91 (69.0 %) elderly people. Of these, 40 (44.0 %) elderly persons felt ageism at least once and 23 (25.2 %) were severely affected at least once. There was no statistically significant difference in affectedness between groups regarding gender (x2 = 13.554, p = 0.825), education (x2 = 20.807, p = 0.409) and age (x2 = 19.328, p = 0.501). Discussion and conclusion: The study has demonstrated a significant presence of ageism in a clinical setting. Since ageism has a negative impact on the relationship towards the elderly and the quality of care, it is necessary to implement basic methods of communication with the elderly in education programs of all healthcare professionals.
Keywords: discrimination; diskriminacija; elderly; healthcare professionals; predsodki; prejudice; starostniki; zdravstveni delavci